ANALISIS PERTIMBANGAN DAN TANTANGAN TEKNIK SETTING SOUND SYSTEM STUDI KASUS PADA OPERATOR SOUND DI ACARA IBADAH RAYA GBI PERMATA SIPOHOLON - Beriman Simatupang; Andar Gunawan Pasaribu; Rowilson Nadeak; Boho Parulian Pardede; Aprinaldi P. Simarangkir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sound quality is a crucial element in the effectiveness of liturgical message delivery in the church. This study aims to analyze the technical considerations and operational challenges faced by sound system operators during Sunday Services at GBI Permata Sipoholon. Using a qualitative approach with a case study method, data were collected through participant observation, in-depth interviews, and documentation of audio setup practices in the field. The results indicate that strategic operator considerations include gain structure adjustment, frequency balancing, and speaker placement management to control sound reflections (feedback and reverberation). The primary challenges identified include room acoustic fluctuations, hardware limitations, and the need for rapid decision-making during technical anomalies or sudden changes in worship dynamics. This study concludes that successful audio output depends not only on hardware specifications but also on the tactical competence and musical sensitivity of the operator in creating a solemn worship atmosphere. Adaptive technical setup innovations proved to be a determining factor in maintaining sound clarity and congregational audial comfort.